Strategic synthesis of mesoporous Pt-on-Pd bimetallic spheres templated from a polymeric micelle assembly. Issue 23 (26th May 2016) - Li, Yunqi; Li, Cuiling; Bastakoti, Bishnu Prasad; Tang, Jing; Jiang, Bo; Kim, Jeonghun; Shahabuddin, Mohammed; Bando, Yoshio; Kim, Jung Ho; Yamauchi, Yusuke
Abstract : Core–shell–corona type triblock copolymer poly(styrene- b -2-vinylpyridine- b -ethylene oxide) (PS- b -P2VP- b -PEO) micelles have been selected here to direct the synthesis of mesoporous Pt-on-Pd spheres. Abstract : Core–shell–corona type triblock copolymer poly(styrene- b -2-vinylpyridine- b -ethylene oxide) (PS- b -P2VP- b -PEO) micelles have been selected here to direct the synthesis of mesoporous Pt-on-Pd spheres, consisting of a Pd concentrated core and a Pt shell, as established by elemental mapping. It is important to note that the size of the PS core determines the resultant size of the mesopores. A self-evaporation method has been developed to prepare swollen micelles, so as to further enlarge the pore size (∼40 nm). Compared with commercially available catalysts ( e.g., Pt black or Pt, 20 wt% on carbon black), good oxygen reduction reaction performance on the mesoporous Pt-on-Pd spheres is observed, due to the exposure of the most active Pt (111) planes and the synergistic effects from Pt and Pd in the pseudo core–shell structure.